Factors of the Rise and Fall of Human Civilization based on the Perspective of Al- Quran - Mat @ Mohamad, Mohamad Zaidin; Ibrahim, Basri; Salleh, Abdul Wahid; Yusof, Sofyuddin (2013)
Al-Quran was sent down to organize human’s life in various aspects of life from ibadah matters to human relations between nations, based on the guidelines sent down by Allah. It also serves as a guide to show all mankind towards the right path and to avoid them from the darkness (or the absence of light). It contains explanation on faith, knowledge, worship to Allah, economic principles, relationship between nations, social relationship, warfare and peacemaking and country’s regulations as well as stories of previous mankind and the civilization they built in this world. In explaining about the regulations of developing life, al-Quran presents the factors that contribute to the rise and fall or collapse of civilization of a certain nation in the world. These factors are important to be studied and pondered on by all mankind in this world so that the collapse of civilization of previous mankind will not repeat itself in this era. The rise of human civilization is not limited solely to material development but it also involves mental and spiritual development.